The Impact of Knowledge-Sharing Behaviors in Facilitating Digital Entrepreneurship Among Staff Members. A Survey Research Was Conducted at University Libraries Across the Middle Euphrates Area. - Aladilee, Dr.Omaima Hameed (Indonesian Journal of Public Policy Review, 2026)
General Background: Knowledge sharing has become a critical organizational practice in modern institutions as digital transformation reshapes how employees collaborate, learn, and develop entrepreneurial capabilities in the digital environment. Specific Background: Within university libraries, staff members increasingly rely on knowledge exchange mechanisms such as written contributions, organizational communication channels, personal encounters, and communities of practice to support digital-oriented work processes and professional development. Knowledge Gap: Despite the growing relevance of knowledge sharing for institutional development, empirical evidence describing how different knowledge-sharing behaviors relate to digital entrepreneurship dimensions in academic library settings remains limited. Aims: This study examines knowledge-sharing behaviors and their association with digital entrepreneurship among staff members in governmental university libraries in the Middle Euphrates region. Results: Using survey data from 114 library employees and statistical analysis, the findings indicate that organizational communication represents the most prominent knowledge-sharing dimension, supported by formal mechanisms such as periodic meetings, work reports, and established communication channels that function as primary sources of knowledge exchange among staff. Conversely, digital creation and innovation appear as the least represented dimensions within the examined libraries, indicating limitations in innovative digital practices. Novelty: The study provides empirical evidence linking structured knowledge-sharing practices with multiple dimensions of digital entrepreneurship in university library institutions. Implications: These findings highlight the administrative importance of formal communication systems as foundations for institutional knowledge circulation and suggest opportunities for future managerial initiatives aimed at strengthening digital innovation capacities within academic libraries. Highlights:• Formal Institutional Channels Act as the Primary Mechanism for Internal Knowledge Exchange Among Library Staff.• Innovative Digital Creation Activities Remain the Least Represented Capability in the Surveyed Institutions.• Survey Data From 114 Employees Reveal Patterns of Digital Entrepreneurial Capacity Within Academic Library Workplaces. Keywords: Knowledge Sharing Behavior, Digital Entrepreneurship, University Libraries, Organizational Communication, Digital Innovation.